Assessing Efficiency and Image Quality of Dental Radiography Using Modified Dental Holders with Silicone Rubber Integration - Jannah, Marichatul; Mulyati, Sri; Gandhi, Wingghayarie Patra (Poltekkes Kemenkes Semarang, 2023)
This study aims to evaluate the efficiency of use by radiographers and image quality in the use of dental holders that have been modified with silicone rubber in dental radiography procedures. Motivated by the problem in the use of conventional dental holders that often cause discomfort for patients and the potential for motion artifacts, a modification with silicone rubber was proposed. The study sample involved 16 repetitions on each head cadaver using both the innovative and control dental holders. The results of the paired t-test showed a significant difference in efficiency of use by radiographers and image quality between the two groups. The efficiency of use by radiographers increased, supported by a Cohen's d value of 9.632. The modification with silicone rubber showed better images, with a Cohen's d value of 0.325, attributed to the adjustable conus guide capability according to the size of the patient's mouth and jaw as well as the increased comfort with the silicone rubber material. This study recommends the adoption of the modified dental holder to improve procedure efficiency and quality of dental radiography results.